Conducting polymer-carbon nanotubes composite as electrocatalysts support for fuel cell application. - Tan, Isa Yingxi. (2009)
Palladium (Pd) nanoparticles were loaded onto multi-walled carbon nanotubes (MWCNTs) that were functionalized by poly(sodium 4-styrene sulphonate)(PSS) (abbreviated Pd/PSS-MWCNTs) and its performance as anode catalysts for formic acid electro-oxidation was examined by cyclic voltammetry (CV) technique. It was found that such non-covalent functionalization of MWCNTs was more effective in giving Pd catalyst better performance for formic acid oxidation than conventional functionalization by acid oxidation. The better electrocatalyst activity is attributed to (i) less structural damages to the PSS/MWCNT support, (ii) higher electrochemically active surface area (ECSA) of smaller Pd nanoparticles formed due to released sulphonated phenyl anion group from PSS (iii) higher ECSA of smaller Pd nanoparticles formed due to increase in surface functional groups and (iv) the reduction in adjacent sites for formation of poisoning species. In addition, such functionalization was found to allow high mass activity for formic acid oxidation at high Pd loading. The increased activity for increasing Pd loading is attributed to (i) the increase in defect sites and grain boundaries which provide sites for the removal of poisoning intermediate species and (ii) the increase in Pd(111) plane that were more active for formic acid oxidation. Lastly, the pH used during the reduction of precursors onto PSS-MWCNTs was found to affect the size and morphology of Pd nanoparticles formed. When a higher pH was used, a lower ECSA and hence a decrease in catalytic activity was generally observed. This is attributed to the interference of OH- at high pH values which results in a low nucleation rate and hence agglomeration of Pd nanoparticles.